PERANCANGAN MULTI BAND POWER AMPLIFIER CLASS-E PADA FREKUENSI 900 MHz, 1800 MHz, 2300 Mhz, dan 2600 Mhz - Ferri Julianto; Irawati Irawati (JEIS: Jurnal Elektro dan Informatika Swadharma, 2021)
In this research is designed High efficiency Concurent Multiband RF Power Amplifier Class-E with 0.18 m CMOS type N, which operates at GSM 900 MHz, GSM 1800 MHz, WIMAX 2300 MHz, and LTE 2600 MHz, using two method of design. First design is using a Conventional Multiband Power Amplifier Class-E and the second design is by adding a Driver Stage to the circuit to achieve much higher Insertion loss. The input matching and output matching is design using lumped component. the aim of this design is to achieve result of Insertion loss) above 15 dB and Return loss below -15 dB, supply voltage 5 V, power added efficiency above 50%, this design is simulated using Advanced Design System (ADS). The simulation results using a driver stage circuit shows that S21 of 21.934 dB, 25.581 dB, 21.798 dB, dan 19.997 dB was obtained at 900MHz, 1800MHz, 2300MHz, and 2600MHz. And S11 of -15.270 dB, -24.404 dB, -19.974 dB, and -16.584 dB was obtained at 900MHz, 1800MHz, 2300MHz, and 2600MHz. In terms of maximum PAE was obtain 52.98% at those frequencies.